The Relationship of Leadership Effectiveness towards Volunteers Behavior in Tzuchi Foundation Medan Branch: Hubungan Efektivitas Kepemimpinan Terhadap Perilaku Relawan di Yayasan Tzuchi Cabang Medan - Edward Harnjo; Javerson Simamora; Diana Afriani; Gloria (Jurnal Kolaboratif Sains, 2023)
Nowadays, Indonesia is living in a world of growth and competition. Therefore, leadership is vially important at all levels within the company. An effective leadership must develop the leadership qualities among individuals within the organization. To learn more about leadership effectiveness in volunteers ‘behavior improvement, the writer chose the title of skripsi, “The Relationship Leadership Effectiveness Towards Volunteers Behavior in TzuChi Foundation Medan Branch” Leadership effectiveness is concentrated in personal perception and personal judgment of others, subordinates’ satisfaction, goal attainment, preparedness to address challenges or crisis, types of decisions and implementation of change. And to volunteers’ behavior is concentrated in job task fulfillment, working relationships, innovative spirit, individual creativity, personality, ethical thinking, professional and social responsibility. Resarch design that writer used is descriptive method and casual method. After getting the data, the writer makes the tabulation to calculate and analyse it to determine the mean, meridian, mode, correlation, validation, reliability, normality, linear regression, determination and test of hypothesis. The results obtained by the writer is Leadership Effectiveness towards Volunteers’ Behavior at TzuChi Foundation Medan Branch.